LncRNA LINC01088 inhibits the function of trophoblast cells, activates the MAPK-signaling pathway and associates with recurrent pregnancy loss. (15th July 2021) - Zhao, Hui; Li, Yali; Dong, Nana; Zhang, Lei; Chen, Xi; Mao, Huihui; Al-Ameri, Samed Ahmed Al-Ezzi; Wang, Xiaoling; Wang, Qun; Du, Lutao; Wang, Chuanxin; Mao, Haiting
Abstract: Long noncoding RNAs (lncRNAs) have been reported to be involved in various cellular processes and to participate in a variety of human diseases. Recently, increasing studies have reported that lncRNAs are related to many reproductive diseases, such as pathogenesis of recurrent pregnancy loss (RPL), preeclampsia (PE) and gestational diabetes mellitus (GDM). In this study, we aimed to investigate the effect of LINC01088 in trophoblast cells and its potential role in pathogenesis of RPL. LINC01088 was found to be upregulated in first-trimester chorionic villi tissues from RPL patients. Increased LINC01088 repressed proliferation, migration and invasion of trophoblast cells, and promoted apoptosis of trophoblast cells. Further exploration indicated that LINC01088 decreased the production of nitric oxide (NO) by binding and increasing Arginase-1 and decreasing eNOS protein levels. Importantly, JNK and p38 MAPK-signaling pathways were active after overexpression of LINC01088. In conclusion, our studies demonstrated that LINC01088 plays an important role in the pathogenesis of RPL, and is a potential therapeutic target for the treatment of RPL.